Analisa Algoritma Kecepatan Pengulangan / Loop dengan While dan For dalam Visual Foxpro 9.0 - Harmon, Harmon (Jurnal Informatika dan Komputasi STMIK Indonesia Jakarta, 2010)
When we are going to develop an information system, it is always to seek one thing which will be quicker to process its data efficiently. It is a normal hope, but it must be supported how much cleverer to chose an exact control-structure statement.   In developing information system, it means to create many computer programs even so hundreds programs not often to face some conditions which must be repeated to complete the data process. In a computer program is always built by many statements and by up to thousands statements, and a group statement sometime must be repeated n times, so it could be imagine to make the computer programs need much time to process data. That is why to look for the way of repeating much more quickly. Keywords: It is often to face some conditions which must be repeated to complete the data process. So how to look for the way of repeating much more quickly